A standard orthography for non-standard English? - Maček, Dora (Array, 2000)
In an etymological spelling such as English, in order to show dialectal features of a character's speech writers use non-standard spelling (eye dialect) which has a long tradition in English literature. Dealing with eye dialect diachronically and synchronically, it is shown that dialect is not represented in a maximally accurate way, but approximated in varying degrees. Although variant spellings for different features can be observed throughout (inconsistencies occur inside one work and in the whole corpus), standardizing tendencies can be observed, which, together with the semantic and syntactic context, make eye dialect more intelligible for the average reader.